Diseño e implementación de un banco didáctico para pruebas en motores Diésel, con aplicación de estudio en la Universidad Antonio Nariño-Tunja. (2020)
This document describes the fundamental criteria in the design and implementation of a test bench for a diesel engine, and subsequently the description of the processes developed for its construction. In the design phase: the most important factors to consider are ergonomic and operator safety, thus guaranteeing a flexible and reliable bank during its operation, for this, study tests are carry out on the design of the systems and subsystems of the bank through programs such as Autodesk Inventor, the structure design is validated through load simulations, and thus ensure that the bank dimensions are structurally correct for its operation. The aesthetic is an important factor to consider at the time of construction, as well as manufacturing processes easily accessible at a low cost.